Karakteristik ibu hamil yang melakukan tindakan sectio caesarean di rumah sakit sitti khadijah makassar periode 2019 - 2021 - Alfian Fadli; Masita Fujiko; Sri Wahyuni Gayatri; M. Hamsah; Rachmat Faisal Syamsu (Universitas Muslim Indonesia, 2023)
All women want to give birth well and perfect parturition. There are two methods of parturition, namely vaginal parturition, which is better known as natural parturition, and caesarean section, in which the baby is removed through an incision in the abdominal wall and uterus. The number of caesarean deliveries in Indonesia continues to increase in 2018. Cesarean procedures account for 17.6% of all deliveries in Indonesia, exceeding the WHO standard of 15%. To find out the characteristics of pregnant women who perform caesarean sections at Sitti Khadijah Hospital Makassar for the period 2019 - 2021. An observational study with a descriptive approach, a cross-sectional study was used as the research design. There were 100 pregnant women who had Caesarean Sections at Sitti Khadijah Hospital Makassar for the period 2019-2021. The results showed that the characteristics of pregnant women who had Caesarean Sections based on the highest age was 20-35 years as much as 69% compared to other age groups, based on education the highest was undergraduate as much as 41% compared to other educational groups, based on work the highest were patients who did not work as much as 65% compared to patients who worked as much as 35%, based on medical indications the highest were Post SC patients as much as 38%, based on the highest type of SC is a patient with SSTP of 96% compared to Classic SC of 4%, based on parity, the highest were patients who were multiparous as much as 73% compared to primiparas as much as 27%. Pregnant women who did caesarean section based on the most age were aged 20-35 years, the most education was undergraduate, the most jobs were pregnant women not working, the most medical indications were pregnant women with a history of post SC, the most type of SC was SCTP, and the most parity was multiparous pregnant women